Case Report: Increased FGF23 and new insufficiency fractures at burosumab discontinuation in X-linked hypophosphatemia - Bandir, Robert; Zanisi, Laura; Nicod-Lalonde, Marie; Gonzalez-Rodriguez, Elena (Frontiers in Endocrinology, 2025)
Burosumab, a monoclonal antibody that binds and inhibits FGF23 activity, was approved in 2018 for treatment of children and adults with X-linked hypophosphatemia (XLH), an X-linked dominant disorder due to increased serum fibroblast growth factor 23 (FGF23) concentration. XLH presents with chronic hypophosphatemia that provokes rickets and dental complications in children, which persist in adults accompanied by bone pain, insufficiency fractures, and enthesis calcifications. Historically, treatment relied on oral phosphate and active vitamin D supplementation. Randomized clinical trials have shown that burosumab allows for hypophosphatemia correction and significant improvement of clinical symptoms in both children and adults. Moreover, fracture healing is 16.8 times higher compared with placebo-treated patients. However, optimal treatment duration has not been determined, and there are few data on clinical, biological, or radiological consequences of burosumab discontinuation. We present the case of a 36-year-old young woman with XLH and disability in the context of chronic bilateral femoral shaft fractures progressing despite optimal phosphate and calcitriol supplementation. After only three burosumab doses, fracture lines were no longer visible on X-rays and the patient could stop pain killers. Burosumab was interrupted after 11 months due to lack of insurance reimbursement. Three months after the last injection, a bone scintigraphy performed because of thigh pain recurrence showed healing of previous bilateral femoral fractures and showed the development of a new fracture on the right femoral shaft, in the presence of very high intact FGF23 values (9,330.0 pg/ml; N 10-50; patient values without treatment: 91.4 pg/ml). While burosumab may interfere with FGF23 dosage during treatment, it should be nearly totally eliminated after ≤95 days (half-life ≤19 days), suggesting that FGF23 accumulated under burosumab inducing a very rapid relapse of clinical symptoms. Because in some cases burosumab treatment should be interrupted (end of reimbursement, pregnancy in the absence of safety data), further studies are needed to better explain the FGF23 increased levels after burosumab discontinuation and the clinical, biological, and radiological consequences of burosumab withdrawal.